Investigation on the Influence of Shear on Void Closure in Open‐Die Forging Processes. Issue 11 (1st November 2022) - Gouverneur, Moritz; Bailly, David; Hirt, Gerhard
Abstract : In article 2200327, Gouverneur, Bailly, and Hirtcover, show an ingot made of AISI4140 with artificially introduced voids, forged on the Institute for Metal Forming (IBF) forging press. This setup validates the shear model for void closure in open‐die forging developed in this article.